1991
DOI: 10.1007/bf00634971
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipid concentrations in professional cyclists after competitive cycle races

Abstract: Plasma lipid concentrations were measured in professional cyclists at the beginning of the training season and both before the start and at the end of two cycle races of similar length (800 and 900 km in 6 days). Plasma concentrations of triglyceride, total and low density lipoprotein-cholesterol (LDL-C) and total cholesterol: high density lipoprotein-cholesterol (HDL-C) ratio were significantly lower and HDL-C concentrations significantly higher in cyclists compared to values in matched sedentary controls. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Prolonged exercise may have favourable effects on plasma lipids and lipoproteins and therefore constitute a non-pharmacological approach to lipoprotein therapy (5,7,9,10). Cross-sectional studies have shown that endurance athletes generally have lower concentrations of triacylglycerols, total cholesterol and LDL cholesterol and higher levels of HDL cholesterol (11)(12)(13)26). However, cross-sectional studies have methodological limitations because of genetic differences and differences in life-style of the participants and definite conclusions cannot be drawn (11,13).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Prolonged exercise may have favourable effects on plasma lipids and lipoproteins and therefore constitute a non-pharmacological approach to lipoprotein therapy (5,7,9,10). Cross-sectional studies have shown that endurance athletes generally have lower concentrations of triacylglycerols, total cholesterol and LDL cholesterol and higher levels of HDL cholesterol (11)(12)(13)26). However, cross-sectional studies have methodological limitations because of genetic differences and differences in life-style of the participants and definite conclusions cannot be drawn (11,13).…”
Section: Discussionmentioning
confidence: 97%
“…Cross-sectional studies have shown that endurance athletes generally have lower concentrations of triacylglycerols, total cholesterol and LDL cholesterol and higher levels of HDL cholesterol (11)(12)(13)26). However, cross-sectional studies have methodological limitations because of genetic differences and differences in life-style of the participants and definite conclusions cannot be drawn (11,13). In longitudinal studies, the benefits of exercise on blood lipid and lipoprotein levels are modest and often contradictory (14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several epidemiological studies have revealed that a sedentary lifestyle is an independent risk factor for coronary heart disease, while habitual physical activity may reduce the individual risk for this condition (6,(18)(19)(20)(21). The protective effect of exercise seems to be mediated through favourable influences on several established anthropometric and biochemical risk factors (19,27,33 Vigourous physical activity may directly or indirectly influence body weight, blood pressure and the lipid status (22,24). Furthermore, beneficial effects of intensive exercise on the haemostatic system are described (23,25).…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical exercise, among other life-style habits like diet and a history of no smoking, may reduce the risk of vascular thrombotic events (6,(18)(19)(20)(21). This protection might be mediated through the effect of exercise on the haemostatic system and the lipid metabolism, because endurance trained athletes exhibit generally more favourable values of haemostatic and lipidic variables than their non-active counterparts (22)(23)(24)(25). The results of longitudinal studies, in which selection bias and constitutional factors have been minimized, are difficult to compare due to differences in e. g. duration and intensity of the exercise programmes (23,(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%